Potential Purchasing Decision on Eco-friendly Products: A Study on Electric Motorcycle Consumers - Apriliyanto, Nanang; Gilang Kharisma Putra; Kuwatno (JKBM (JURNAL KONSEP BISNIS DAN MANAJEMEN), 2024)
The aim of this study is to enhance the potential for electric motor purchases by raising public awareness of climate change, thereby supporting government climate action initiatives. This research adopts a quantitative approach, employing a survey method with purposive sampling based on predefined crite-ria. The criteria specify that respondents must be Indonesian citizens aged 17 years or older who have decided to buy an electric motorbike. This resulted in a sample size of 300 respondents. The study's data, collected through surveys, constitute the primary research data. Analysis was conducted using structural equation modeling (SEM) via the SmartPLS application. The study concludes that there is no direct rela-tionship between environmental awareness, perceived value, and green product quality and purchasing decisions for electric motor products. Conversely, there is a direct and significant positive relationship between environmental awareness, perceived value, and green product quality and trust. Furthermore, trust has a direct, meaningful, and significant impact on purchasing decisions. Additionally, the mediating effect of trust indicates that environmental awareness, perceived value, and green product quality in-fluence purchasing decisions.